Effect of surgical staging on 539 patients with borderline ovarian tumors: A Turkish Gynecologic Oncology Group study - Guvenal, Tevfik; Dursun, Polat; Hasdemir, Pinar S.; Hanhan, Merih; Guven, Suleyman; Yetimalar, Hakan; Ayhan, Ali (Academic Press Inc Elsevier Science, 2013)
Objective. The objectives of this study were to examine demographic and clinicopathologic characteristics and to determine the effects of primary surgery, surgical staging and the extensiveness of staging. Methods. In a retrospective Turkish multicenter study, 539 patients, from 14 institutions, with borderline ovarian tumors were investigated. Some of the demographic, clinical and surgical characteristics of the cases were evaluated. The effects of type of surgery, surgical staging; complete or incomplete staging on survival rates were calculated by using Kaplan-Meier method. Results. The median age at diagnosis was 40 years (range 15-84) and 71.1% of patients were premenopausal. The most common histologic types were serous and mucinous. Majority of the staged cases were in Stage IA (735%). 242 patients underwent conservative surgery. Recurrence rates were significantly higher in conservative surgery group (8.3% vs. 3%). Of all patients in this study, 294 (545%) have undergone surgical staging procedures. Of the patients who underwent surgical staging, 228 (77.6%) had comprehensive staging including lymphadenectomy. Appendectomy was performed on 204 (37.8%) of the patients. The median follow-up time was 36 months (range 1-120 months). Five-year survival rate was 100% and median survival time was 120 months. Surgical staging, lymph node sampling or dissection and appendectomy didn't cause any difference on survival. Conclusion. Comprehensive surgical staging, lymph node sampling or dissection and appendectomy are not beneficial in borderline ovarian tumors surgical management. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Borderline; Ovarian tumor; Lymphadenectomy; Appendectomy; Surgical staging